ショウワ キチ フキン ロガン チイキ ノ チケイ - 小疇, 尚; コアゼ, タカシ; KOAZE, Takashi (国立極地研究所, 1964)
P(論文) The bare rock areas along the eastern coast of Lutzow-Holm Bay are topographically classified into (1) strandflat, (2) hilly lands, (3) mountains, and (4) recessional moraines, which had been described as divisible into two: hilly lands and mountains (YOSHIKAWA and TOYA, 1957), or flat surface and mountains including hilly lands (TATSUMI and KIKUCHI, 1959a). (1) The marginal belt of Langhovde and Skarvsnes areas, the Ongul Islands and many other coastal islets, formerly described as flat surface are as a whole regarded as strandflat. It rarely attains to 50 metres and in most cases to less than 30 metres in height above sea level. Judging from its topographical characteristics it is considered to be a glaciated piedmont plain (Plate 1). (2) The hilly lands attaining to 50-300 metres in height and showing as a whole an accordance of summit level are regarded as roches moutonnees of a rather large scale, among which there are many cirque-like hollows, small-scale U-shaped valleys and steep-sided inlets formed by the differential erosion of ice sheet or by the erosion of ice falls and or ice streams (Plates 1 and 2). (3) The mountains, 300-500 metres high above sea level, which dominate over the surrounding hilly lands have an appearance of so-called "giant roche moutonnee" or glaciated monadnock (Plate 3). In some places, mountain flanks are almost vertically truncated by the lateral erosion of ice streams as in the northern face of Mt. Langhovde, the southwestern wall of Mt. Skjegget and the southwestern part of Breidvognippa. (4) A series of recessional moraines, 5-30 metres wide and 100-1,000 metres long, occur at a distance of 10-100 metres landward from the inner margins of the actual bare rock areas (Plate 4). At present, these moraines indicate the position of the boundary between the "dead" and the "active" glacier ice. No morainic hillock other than these and no meltwater drainage channel could thus far be found on the bare rock areas. These facts imply that the front of the former ice sheet ...